Medication Safety and Accessibility: The Impact of Pharmacists on Public Health Policies and Patient Care - Maram Khaled Ahmed AlThabet; Raod Ali Zaied Alshahrani; Wafa Saeed Mohammed Alshahrani; Amjad Msfer Awad Al Almunis; Thuraya Yahya Ebrahem Asiri; Tahani Ali Mubarak Alqahtani; Amal Saeed Naseer Al Ghunum; Alanoud Nasser Zamil Alshahrani; Mohammed Safar Mohammed Alshahrani; Abdalrhman Hassan Ali Alassiri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Medication safety and rational use is an important component of health care systems worldwide to achieve the best therapeutic effect with fewer adverse effects of using medications. HIS is therefore not only beneficial to the general health of a nation’s population but also a way through which costs of health care, hospitalization and even adverse drug reactions which are some of the biggest killers globally can be reduced. In this regard, the pharmacist occupies an essential function as medication experts, and participating members of public health and patient safety and accessibility society programs. Aim of work: To highlight the challenges and opportunities in these domains, emphasizing the need for integrated approaches to optimize healthcare delivery and improve patient outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Medication Safety, Accessibility, Impact, Pharmacists, Public, Health, Policies and Patient Care. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Basically, pharmacists are valuable partners in medication safety; they play their part to avoid medication errors, teach patients and prescribers, and identify adverse drug effects. They contribute at both micro and macro levels and are invaluable members to ensuring the safe delivery of medicines to individual patients. To build on this success, there are factors that health systems need to overcome including workload and other factors concerning system integration to allow pharmacists operate at their maximum capacity as medication safety communicators. With the help of the discussed measures involving pharmacists’ safety performance and promoting interdisciplinary cooperation, health care organizations are able to decrease medication related harm in rather a short period of time, thus enhancing patient and population health.